Strategi Komunikasi Affiliator Pada Program Tiktok (Studi Kasus Pada Akun Tiktok @Yogaade): Studi Kasus Pada Akun Tiktok @Yogaade - Putri, Rossy; Wangi, Maya Sekar; Rizqi, Fikriana Mahar (Solidaritas, 2024)
Abstract The purpose of this study is to describe the communication strategy carried out by affiliators in the TikTok program in order to influence user behavior in following and buying products recommended by affiliators on the TikTok @yogaade account. The research uses an approach with the theory of Anwar Arifin, which includes steps such as knowing the audience, determining the message, determining the method, determining the media. The type of research used in this research is descriptive qualitative research. Data collection techniques in this research are using participant observation methods, interviews and documentation. Data analysis techniques use data collection, data reduction, data presentation and conclusion drawing or verification. Based on the research results obtained, Yoga Ade recognizes its audience through audience segmentation, understanding User Persona, and conducting keyword research. Yoga Ade determines its content message by considering the purpose of the content, the value of the brand being promoted, and understanding the target audience. His content methods involve creating engaging content, content schedules, using social tools, content analysis, social media audits, competition monitoring, and keyword identification. By choosing TikTok as a media platform as an affiliator, Yoga Ade managed to reach his audience of mainly 18-30 year olds, especially women. Despite his success, he has also experienced obstacles such as uncertainty. Keywords: Communication Strategy, TikTok, Affiliator, Knowing The Audience, Determining The Message, Determining The Method, Determining The Media